1975
DOI: 10.1104/pp.55.6.1071
|View full text |Cite
|
Sign up to set email alerts
|

Stereoisomeric Characterization of Tartaric Acid Produced during l-Ascorbic Acid Metabolism in Plants

Abstract: Labeled tartaric acids from Pelargoniunt crispum apices which had been fed L-ascorbic acid-6-"C and Vitis labrusca and Parthenocissus inserta tissues which had been fed L-ascorbic acid-l-"4C were examined by chemical means to determine chiral configuration. In each instance, label was associated with (+)-tartaric acid.Similar experiments with labeled tartaric acid from P.crispuom which had been labeled with D-glucose-l-"C or -6-'4C led to the same result. No evidence was obtained for formation of labeled meso-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…By feeding labeled Asc to immature berries of a number of species from the Vitaceae family it was determined that [1- 14 C]Asc and [4- 14 C]Asc corresponded to the C1 and C4 carbons respectively of the TA skeleton ( Williams and Loewus, 1978 ). Earlier studies that identified the key intermediates and organization of the C4/C5 pathway ( Saito and Kasai, 1969 ; Wagner and Loewus, 1974 ; Wagner et al, 1975 ) were complemented by later work identifying the final intermediates ( Saito and Kasai, 1982 , 1984 ). Accumulation of radiolabeled L-idonate in grapevine leaves also fed with labeled Asc confirmed that the oxidation of L-idonate to 5-keto-gluconic acid is a rate-limiting step of TA synthesis ( Malipiero et al, 1987 ).…”
Section: Biosynthetic Enzymes Of Tartaric Acidmentioning
confidence: 99%
“…By feeding labeled Asc to immature berries of a number of species from the Vitaceae family it was determined that [1- 14 C]Asc and [4- 14 C]Asc corresponded to the C1 and C4 carbons respectively of the TA skeleton ( Williams and Loewus, 1978 ). Earlier studies that identified the key intermediates and organization of the C4/C5 pathway ( Saito and Kasai, 1969 ; Wagner and Loewus, 1974 ; Wagner et al, 1975 ) were complemented by later work identifying the final intermediates ( Saito and Kasai, 1982 , 1984 ). Accumulation of radiolabeled L-idonate in grapevine leaves also fed with labeled Asc confirmed that the oxidation of L-idonate to 5-keto-gluconic acid is a rate-limiting step of TA synthesis ( Malipiero et al, 1987 ).…”
Section: Biosynthetic Enzymes Of Tartaric Acidmentioning
confidence: 99%
“…Plants, especially higher plants, produce all three stereoisomeric forms of tartaric acid [19] (Fig. 1.a).…”
Section: Mono-and Disaccharidesmentioning
confidence: 99%
“…meso-tartaric acid [22,49,75,76], erythritol [77], butanediol [78], galactitol [26,79], allitol [80], xylitol [81], ribitol [82,83], allaric acid [84], xylaric acid [85], ribaric acid [86], galactaric acid [26], D-galactitol-3R,4Scinnamicacetal [87], galaoctitol [88][89][90].…”
Section: Monosaccharidesmentioning
confidence: 99%